2007 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--1737
|View full text |Cite
|
Sign up to set email alerts
|

From Tootsie Rolls To Composites: Assessing A Spectrum Of Active Learning Activities In Engineering Mechanics

Abstract: National Lab and MacNeal-Schwendler Corp. His research includes development of innovative design methodologies and enhancement of engineering education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Klosky and Vander Schaaf [11] and Lanning and Roberts [14] both reported significant improvements in student ratings of the course and instructor in semesters where demonstrations were used compared to previous semesters when they were not. In several studies [7], [9], [10], [13], [17] student ratings of the effectiveness of demonstrations or activities were generally on the positive side (as opposed to the negative side) of neutral, with ratings of generally 3.5 to 4 (4.5 to 5 in one study) on a 5-point Likert scale where 3 is neutral, 4 is agree and 5 is strongly agree that they were effective. Two studies [7], [8] also looked at changes in student performance on quizzes and exams when demonstrations were used in class compared to when they were not.…”
Section: Previous Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Klosky and Vander Schaaf [11] and Lanning and Roberts [14] both reported significant improvements in student ratings of the course and instructor in semesters where demonstrations were used compared to previous semesters when they were not. In several studies [7], [9], [10], [13], [17] student ratings of the effectiveness of demonstrations or activities were generally on the positive side (as opposed to the negative side) of neutral, with ratings of generally 3.5 to 4 (4.5 to 5 in one study) on a 5-point Likert scale where 3 is neutral, 4 is agree and 5 is strongly agree that they were effective. Two studies [7], [8] also looked at changes in student performance on quizzes and exams when demonstrations were used in class compared to when they were not.…”
Section: Previous Studiesmentioning
confidence: 99%
“…In several studies [7], [9], [10], [13], [17] student ratings of the effectiveness of demonstrations or activities were generally on the positive side (as opposed to the negative side) of neutral, with ratings of generally 3.5 to 4 (4.5 to 5 in one study) on a 5-point Likert scale where 3 is neutral, 4 is agree and 5 is strongly agree that they were effective. Two studies [7], [8] also looked at changes in student performance on quizzes and exams when demonstrations were used in class compared to when they were not. Linsey et al [7] found a greater improvement between student performance on pre-and post-topic quizzes for an experimental group that used active learning demonstrations compared to a control group that did not.…”
Section: Previous Studiesmentioning
confidence: 99%
See 3 more Smart Citations